Reversible Immobilization of Proteins in Sensors and Solid‐State Nanopores. Issue 18 (3rd April 2018) - Ananth, Adithya; Genua, María; Aissaoui, Nesrine; Díaz, Leire; Eisele, Nico B.; Frey, Steffen; Dekker, Cees; Richter, Ralf P.; Görlich, Dirk
Abstract: The controlled functionalization of surfaces with proteins is crucial for many analytical methods in life science research and biomedical applications. Here, a coating for silica‐based surfaces is established which enables stable and selective immobilization of proteins with controlled orientation and tunable surface density. The coating is reusable, retains functionality upon long‐term storage in air, and is applicable to surfaces of complex geometry. The protein anchoring method is validated on planar surfaces, and then a method is developed to measure the anchoring process in real time using silicon nitride solid‐state nanopores. For surface attachment, polyhistidine tags that are site specifically introduced into recombinant proteins are exploited, and the yeast nucleoporin Nsp1 is used as model protein. Contrary to the commonly used covalent thiol chemistry, the anchoring of proteins via polyhistidine tag is reversible, permitting to take proteins off and replace them by other ones. Such switching in real time in experiments on individual nanopores is monitored using ion conductivity. Finally, it is demonstrated that silica and gold surfaces can be orthogonally functionalized to accommodate polyhistidine‐tagged proteins on silica but prevent protein binding to gold, which extends the applicability of this surface functionalization method to even more complex sensor devices. Abstract : A novel method to functionalize silica‐based surfaces is introduced. It allows selective and stable but reversible immobilization of polyhistidine‐tagged proteins with controlled orientation and tunable surface density. The reusable coating retains functionality upon long‐term storage in air, is applicable to surfaces of complex geometry including nanopores, and can be combined with orthogonal functionalizations on gold.